Boiling Heat Transfer and Critical Heat Flux Enhancement Using Electrophoretic Deposition of SiO2 Nanofluid - Aref Rahimian; Hosein Kazeminejad; Hosein Khalafi; Azam Akhavan; Seyed Mohammad Mirvakili (Science and Technology of Nuclear Installations)
The electrophoretic deposition (EPD) technique was used to create a uniform SiO2 thin film coating on boiling plates, 4 mm in width and 9 mm in length. Significant enhancement in critical heat flux (CHF), for the hydrophilic surfaces generated by this anodic EPD method, has been observed. In order to increase the coating strength, the plates were sintered at various temperatures. To find the thickness and uniformity of the coatings, the SEM images were captured. The captured images showed that the coating thickness uniformly increased up to 90 nm for 0.5% nanofluid percentage by the EPD method. The results show that the hydrophilic and super-hydrophilic surfaces have different boiling heat transfer (BHT) coefficients and CHF behaviors. Also, the results showed an increase of 160% in the CHF value by sintering compared to a bare surface. However, because of the setup simplicity, the shape independency, the particle-coating uniformity, and thickness controllability, the EPD technique can be an appropriate option for modification of the surface and coating on the nuclear fuel cladding.